A Decolonizing Care Approach for Those Experiencing the Intergenerational and Transnational Transmission of Historical Trauma - Lee, Hee Jin (Journal of pastoral theology, 2025)
This study explores a decolonizing care approach for addressing the trauma of historically marginalized individuals who are the succeeding generations of those who have experienced trauma from colonialization and war. Since universalized and Western-centric trauma theories are limited in their application to the traumas of such individuals, this research study utilized a survey based on the Adverse Childhood Experiences Study questionnaires, along with narrative inquiry, to unpack the multilayered trauma stories of young Korean descendants who had experienced childhood trauma. Through these persons’ narratives, I found that attributing domestic violence solely to Confucianism is an oversimplified approach and that unresolved historical trauma can create a culture of collective silence and aggression, which causes more trauma. Additionally, I explore the transmission of intergenerational trauma transnationally as part of a decolonizing care approach to understanding the trauma of the succeeding generations of colonialism, imperialism, and war.